Validation of the Chinese Social Constraints Scale Among Malaysian Chinese Postpartum Mothers - Low, Su Rou; Bono, Suzanna Awang; Azmi, Zaireeni; Engku Ismail, Engku Husna (Malaysian Journal of Medical Sciences, 2026)
Background: In Chinese and collectivist cultures, discussing personal feelings is often considered inappropriate or discouraged, even for postpartum mothers. As a self-reported measure of social responses that inhibit the expression of stressful thoughts, feelings, and experiences, the Social Constraints Scale has been widely validated among cancer and bereaved populations, leaving postpartum mothers unattended.Methods: This study aimed to assess the psychometric properties of the Chinese version of the Social Constraints Scale (C-SCS) among Chinese postpartum women in Malaysia. A cross-sectional quantitative survey was conducted among 130 Malaysian women in their first postpartum year.Results: Exploratory factor analysis revealed three underlying factors in the C-SCS, explaining 61.16% of the total variance. Confirmatory factor analysis based on a three-factor structure showed the best fit (P < 0.001) after omitting item 3 due to low factor loading. The C-SCS demonstrated excellent reliability with a Cronbach’s alpha value of 0.90 and McDonald’s Omega of 0.90. The three-factor model of the C-SCS exhibited different factor loadings compared with the Greek Social Constraints Scale, suggesting that these differences stem from postpartum and sociocultural contexts.Conclusion: The C-SCS displayed excellent psychometric properties, making it a reliable and valid measure for screening social constraints and identifying help-seeking barriers among postpartum women in Malaysia.